Little America : the war within the war for Afghanistan - Chandrasekaran, Rajiv (New York : Alfred A. Knopf, 2012)
In this book, the author focuses on southern Afghanistan in the year of Obama's surge. This is the story of the long arc of American involvement, and of the campaign to salvage a victory in southern Afghanistan on Obama's watch., and reveals the epic tug of war that occurred between the President and a military that, once on the ground, increasingly went its own way.
Grand Dreams. An enchanting time ; Stop the slide ; Marineistan ; The wrong man ; The road to ruins ; The surge -- Shattered Plans. Bleeding ulcer ; Search and destroy ; Deadwood ; Burn rate ; Allies at war ; Odd man out ; A bridge too far -- Triage. The boss of the border ; A fresh can of whoop-ass ; There was no escaping him ; My heart is broken ; What we have is folly.
"A Borzoi Book"--T.p. verso.
Includes bibliographical references and index.
Keywords: Obama, Barack -- Military leadership; Afghan War, 2001- -- Political aspects -- United States; Internal security -- Afghanistan; United States -- Politics and government -- 2009-; United States -- Military policy; Afghanistan -- Strategic aspects